This study aims to analyze the influence of digital marketing, creativity, and innovation on the competitiveness of batik MSMEs in Jember City. Using a quantitative approach, data were collected from batik MSMEs through questionnaires and analyzed using multiple linear regression analysis. The results show that these three variables have a positive and significant influence on MSME competitiveness. Digital marketing has been shown to improve market access, interaction with consumers, and custome - Fauziyah, Khirunissa Nur; Hermawan, Haris; Rusdiyanto, Rusdiyanto (Universitas Dharmawangsa, 2025)
This study aims to analyze the influence of digital marketing, creativity, and innovation on the competitiveness of batik MSMEs in Jember City. Using a quantitative approach, data were collected from batik MSMEs through questionnaires and analyzed using multiple linear regression analysis. The results show that these three variables have a positive and significant influence on MSME competitiveness. Digital marketing has been shown to improve market access, interaction with consumers, and customer loyalty. MSME creativity plays a crucial role in producing unique batik products that are in line with market trends, while innovation enables MSMEs to create new products and improve existing ones to meet dynamic consumer needs. This study recommends strengthening digital marketing strategies, increasing creativity, and continuously innovating products as keys to maintaining and improving the competitiveness of batik MSMEs amidst increasingly fierce market competition. Support from the government and relevant institutions is also essential to encourage optimal MSME development.